PERANCANGAN FASILITAS KERJA PROSES PEMBUATAN BAKSO PADA USAHA KECIL MENENGAH MORO ASIH - Al Ayubi, Moh Galih; Sri Zetli (Computer Science and Industrial Engineering, 2024)
This study was conducted on employees at UKM Moro Asih, where the process of making meatballs is still carried out without a work table, which can lead to Musculoskeletal Disorders (MSDs) in employees. Through the distribution of the Nordic Body Map (NBM) questionnaire, it was found that 2 out of 3 workers had a "Very High" level of musculoskeletal risk, indicating the need for comprehensive and immediate action. To make improvements, the Rapid Entire Body Assessment (REBA) method was used by designing a work table that fits the employees' body posture. The research results show that the REBA score before using the work table and chair was 7 (moderate risk), while with the proposed work table and chair, the score decreased to 3 (low risk). This significant change indicates that the addition of these facilities effectively reduces the risk of musculoskeletal disorders in employees in the meatball production section.